A comparative study on the rights and protection provided for the fixed-term contract employees between Malaysia and the United Kingdom / Nur Hidayahtul Nabihah Manas ... [et al.] - Manas, Nur Hidayahtul Nabihah; Salleh, Sarilnezam; Othaman, Siti Salwa; Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani (Universiti Teknologi MARA, Shah Alam, 2019)
This research focuses on employment under the fixed-term contract. It is a type of employment which has became a trend among the employers in Malaysia and has displaced the standard form of employment in recent years. It is a type of employment whereby the employees were employed for a specified time or until a particular task is completed. It is also known as temporary employment. The objective of this research is to examine the rights and protection provided for the fixed-term contract employees under the Employment Act 1955 and to set up a legal benchmark by comparing the employment laws in the United Kingdom with the employment law in Malaysia. This research will involve a general overview of the development of the employment laws in Malaysia and the United Kingdom together with the discussion on the problems faced by the fixed-term contract employees in Malaysia. The examination and comparison will enable a solution to prevent exploitation and mistreatment by the employers toward the employees who were employed under the fixed-term contract in Malaysia.